Health-related quality of life of patients bearing diabetes mellitus / Qualidade de vida relacionada à saúde de pacientes com Diabetes Mellitus - Jennifer Vieira Paschoalin Marques; Carla Regina de Souza Teixeira; Maria Lúcia Zanetti; Luciana Kusumota; Tânia Alves Canata Becker; Paula Parisi Hodniki (Universidade Federal do Estado do Rio de Janeiro, 2020)
Objective: The purpose of this study was to investigate the health-related quality of life and clinical parameters of patients with type 2 diabetes mellitus. Methods: This is a cross-sectional study with a quantitative approach, which was undertaken with 73 patients with type 2 diabetes mellitus in a health unit of the Sistema Único de Saúde (SUS) [Brazilian Unified Health System] in Ribeirão Preto city, São Paulo State, Brazil, in 2016. The DQOL-Brazil questionnaire, which covers the domains of satisfaction, impact, social and/or vocational concerns, and concerns about diabetes mellitus, was used for data collection. Results: Most of the participants were female, married, and retired with an average age of 62.7 years old. The domain of vocational and/or social concerns had the best score for quality of life while satisfaction had the worst. The quality of life of patients with altered glycated hemoglobin levels was worse than that of patients without such alterations. For those with unchanged hemoglobin glycated levels, the domain of social and/or vocational concerns had the best quality of life scores while the domain of satisfaction had the worst. Conclusion: The results can help the development of intervention studies and strategic plans in health services.